Thiolated silicone oil: Synthesis, gelling and mucoadhesive properties. (1st April 2015) - Partenhauser, Alexandra; Laffleur, Flavia; Rohrer, Julia; Bernkop-Schnürch, Andreas
Graphical abstract: Abstract: The aim of this study was the development of novel thiolated silicone oils and their evaluation with regard to gelling and mucoadhesive properties. A thiol coupling of 220 ± 14 and 127 ± 33 μmol/g polymer for 3-mercaptopropionic acid (MPA)- and cysteine-coupled silicone oil was determined, respectively. The dynamic viscosity of MPA–silicone raised significantly ( p  < 0.000001) after oxidation with iodine to a maximum of 523-fold within 1 h. During tensile studies, MPA–silicone showed both the highest results for total work of adhesion (TWA) and maximum detachment force (MDF) with a 3.8- and 3.4-fold increase, respectively, compared to the control. As far as the residence time on small intestinal mucosa is concerned, both silicone conjugates were detectable in almost the same quantities for up to 8 h with 56.9 ± 3.3 and 47.8 ± 8.9% of the initially applied conjugated silicone oil. Thiolated silicone oils can be regarded superior in comparison to commonly used silicone oils due to a prolonged retention time in the small intestine as site of action. Gelling and mucoadhesive features are advantageous for antiflatulent as well as mucoprotective biomaterials. Thus, these novel thiomers seem promising for an upgrade of currently available products for the treatment of dyspepsia, reflux oesophagitis and even inflammatory bowel diseases such as ulcerative colitis or Crohn's disease.